Interactive learning: Designing inventory e-module interactive for logistics vocational school - Dwiyanti, Vina; Okitasari, Hanissa; Putra, Davin Arkan Admoko; Alhamda, Nur Aini (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2023)
One of the awareness that has arisen in Indonesia in response to the challenges of Industry 4.0 is the awareness to be able to meet domestic logistics needs through improving and strengthening the national logistics system. This is mandated through the Center of Excellence, where Logistics is one of the areas of expertise included as a target for the Indonesian government. The socialization and demands of Industry and the World of Work (IDUKA) continue to develop and change so the Vocational High School (SMK)'s ability to fulfill them needs to be improved. The purpose of this research is to compile SMK E-modules that need to be aligned with the needs of IDUKA, especially in the field of logistics. This study used a mixed methods approach by conducting interviews (qualitative) and using questionnaires (quantitative) and studies using secondary data in the form of the SMK Logistics curriculum. The output of this research is in the form of the results of graduate training needed by IDUKA in the form of scientific articles published in indexed international journals for the dissemination of results at international scientific seminars, IPRs, and E-modules.